2013
DOI: 10.1111/jam.12283
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tetracycline-resistant bacteria in an urbanizing subtropical watershed

Abstract: Aims: The objective of this study was to determine whether varying levels of urbanization influence the dominant bacterial species of mildly resistant (0Á03 mmol l À1 tetracycline) and highly resistant (0Á06 mmol l À1 tetracycline) bacteria in sediment and water. Also, the level of urbanization was further evaluated to determine whether the diversity of tetracycline resistance genes present in the isolates and the capability of transferring their resistance were influenced. Methods and Results: Sediment and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…Since TRG incidence frequency was more than two‐fold higher in Hog Hammock's, this village was most likely the main contributor to TRGs in the watershed, however, free ranging cattle, high densities of whitetail deer and a large stork and egret rookery may have also contributed. Impact of land use on the occurrence of antibiotic resistance genes in densely populated watersheds (Sullivan and Karthikeyan ), and correlation between antibiotic resistance of animal‐associated E. coli and the density of human populations in animals' vicinities (Skurnik et al . ) have been previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Since TRG incidence frequency was more than two‐fold higher in Hog Hammock's, this village was most likely the main contributor to TRGs in the watershed, however, free ranging cattle, high densities of whitetail deer and a large stork and egret rookery may have also contributed. Impact of land use on the occurrence of antibiotic resistance genes in densely populated watersheds (Sullivan and Karthikeyan ), and correlation between antibiotic resistance of animal‐associated E. coli and the density of human populations in animals' vicinities (Skurnik et al . ) have been previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The Chryseobacterium is highly resistant to several antimicrobial drugs, such as the third generation cephalosporins, aminoglycoside, carbapenemases and tetracycline. [32][33][34] Its drugresistance mechanism is due to the production of b-lactamase induced by chromosomes, except outside the permeable barrier of the bacterial membrane. The Actinotignum was enriched in R1 reactor with the relative abundance increasing from 0.73% to 19.97%, which was probably because the Actinotignum adapted to the operational conditions of the AGSBR technology with time.…”
Section: The Enrichment and Succession Of Microbial Community In Agsbrmentioning
confidence: 99%
“…The Actinotignum became the most dominant genus of AGS in R1-6 and R2-6. The study showed that the bacterial genus could take tetracycline as the carbon source, [32][33][34] which was helpful for removing tetracycline. The Actinotignum is more common than implied by routine cultivation.…”
Section: The Enrichment and Succession Of Microbial Community In Agsbrmentioning
confidence: 99%
“…Interestingly, the use of Nutrient Broth agar for plating resulted in at least a 10-fold reduction in recovery of strains for both feces and manure. Nutrient agar has been previously used in recovering tetracycline-resistant bacteria from soil and water environments (Sullivan and Karthikeyan, 2011;Sullivan et al, 2013), so it is important to note the improved recovery of isolates using BHI or T-Soy media versus Nutrient Broth agar. The use of habitat-simulating medium for manure samples resulted in recovery of strains similar to that of BHI and T-Soy.…”
Section: Bacterial Isolationmentioning
confidence: 99%